The pH modulation by fungal secreted molecules: a mechanism affecting pathogenicity by postharvest pathogens. Issue 1 (2nd January 2016) - Prusky, Dov; Barad, Shiri; Ment, Dana; Bi, Fangcheng
ABSTRACT: A postharvest pathogen can start its attack process as soon as spores land on wounded tissue; other pathogens breach the unripe fruit cuticle, remain quiescent for months until the fruit ripens, and then cause major losses. Postharvest fungal pathogens initiate their development by secreting organic acids or ammonia, which acidify or alkalinize the ambient host environment, respectively. These fungal secreted molecules (SM) modulate the host environment and regulate an arsenal of enzymes in order to increase fungal pathogenicity under any specific conditions. Furthermore, accumulation of these SMs (organic acids and ammonia) is multifunctional and, together with their effect on the ambient pH, they activate virulence factors to further enhance their necrotrophic attack. Interestingly, similar arsenals of genes were detected in species with differing acidifying and alkalizing modes of attack. Recently, the mechanism of switching the acidification and alkalization processes was found to be regulated by the carbon levels present in the host. Based on this regulation process, it will be possible to foresee the fungal activation of acid- and/or alkaline-expressed genes and their contribution to pathogenicity.